Answer:
[tex]r = d (\frac{\sqrt {q_1}}{\sqrt{q_1} + \sqrt{q_2}})[/tex]
Explanation:
Here two charges are placed at distance "d" apart
now the net value of electric field at some position between two charges will be ZERO
so we will have
electric field due to charge 1 = electric field due to charge 2
[tex]E_1 = E_2[/tex]
Let the position where net field is zero will lie at distance "r" from q1
[tex]\frac{kq_1}{r^2} = \frac{kq_2}{(d-r)^2}[/tex]
now we will have
[tex]\frac{(d - r)^2}{r^2} = \frac{q_2}{q_1}[/tex]
now square root both sides
[tex]\frac{d}{r} - 1 = \sqrt{\frac{q_2}{q_1}}[/tex]
now we have
[tex]\frac{d}{r} = \sqrt{\frac{q_2}{q_1}} + 1[/tex]
so we have
[tex]r = d (\frac{\sqrt {q_1}}{\sqrt{q_1} + \sqrt{q_2}})[/tex]